Cyprus : Second Post-Program Monitoring Discussions-Press Release; Staff Report and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Cyprus' Second Post-Program Monitoring Discussions. Cyprus's economic recovery has strengthened. GDP growth has reached 3.9 percent in 2017, with upbeat activity concentrated in construction, tourism and professional services. The unemployment rate has continued to decline at a sustained pace, while moderate price and wage rises have supported competitiveness, helping to contain the increase in the current account deficit, despite higher imports. Improved economic conditions have supported robust fiscal revenue collection, contributing to a sizable primary surplus and a decline in the public debt ratio. The current strong expansion is forecast to extend well into the future, with growth inching up to 4 percent in 2018 and 4.2 percent in 2019.